1657e Predominance of musculoskeletal ailments and allied work-related contributing factors amongst construction labourers of west bengal, india. (24th April 2018) - Chatterjee, Arijit; Dutta, Koumi; Sahu, Subhashis
Abstract : Introduction: An enormous number of labourers engaged in construction industry in India both in organised and unorganised sectors. The construction labourers regularly work for a broadened time frame and they are compiled to maintain adjusted static and dynamic working positions in unbalanced locations during the total time of work which raises the demand of the musculoskeletal system and may lead to work related musculoskeletal ailments. Objective: This study is proposed to investigate the operational position and work related musculoskeletal ailments among the construction workers. One eighty four male workers from various construction sites of West Bengal was indiscriminately taken for this study. Methods: A modified Nordic questionnaire on MSD and the 12 item General Health Questionnaire (GHQ12) were administered on the construction labourers. REBA and OWAS posture analysis techniques were applied to evaluate the awkward postures. At last, discomfort levels of the particular working positions were figured by the use of risk level and BPD scale. Results: From the study it was uncovered that the greater part of the construction labourers frequently in unbalanced and awkward working position and were allied by different work-related contributing factors like pain in low back, neck, and wrist. It has been likewise discovered that there is a significant (p<0.05) association between the intensity of pain feeling, age, year of working experience and risk level of the individual working postures of the labourers. Conclusion: Suitable work-rest schedule, revisions of some working techniques and use of some ergonomically modified tools may decrease the WMSDs and enhance the health eminence and wellbeing distinction of construction labourers in unorganised sectors.